Update on the Diagnosis and Treatment of Idiopathic Intracranial Hypertension - Ahmad, Sarah R.; Moss, Heather E. (Seminars in Neurology, 2019)
Advances in ophthalmic diagnostics and results of interventional clinical trials are shifting diagnosis and management of idiopathic intracranial hypertension (IIH) to be more technology- and evidence-based. In this article, the evidence supporting current diagnostic criteria, evaluation, and medical and surgical management of IIH are reviewed.
Keywords: Idiopathic intracranial hypertension; pseudotumor cerebri; papilledema